1990
DOI: 10.1364/ol.15.000956
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearity difference in the two passbands of a distributed-feedback semiconductor laser amplifier

Abstract: The nonlinearity difference in the two passbands of a distributed-feedback semiconductor laser amplifier was studied experimentally. A theoretical explanation was given by using the transmission matrix approach. The difference of nonlinearity in the two passbands was found to be enhanced greatly by the mechanism of asymmetric facet reflection.Active optical bistability in Febry-Perot (FP) and distributed-feedback (DFB) semiconductor laser amplifiers has the advantages that the power required for switching is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This iteration procedure is continued until convergence (we refer the reader to [14] for further details). Although neglected in this paper, finite facet reflectivities may be included using appropriate matrices [17].…”
Section: B Computational Analysismentioning
confidence: 99%
“…This iteration procedure is continued until convergence (we refer the reader to [14] for further details). Although neglected in this paper, finite facet reflectivities may be included using appropriate matrices [17].…”
Section: B Computational Analysismentioning
confidence: 99%
“…A pronounced spike in the output transient response of a bistable DFB-SLA with a uniform grating was observed by Adams and Wyatt [4]. Hui and Sapia demonstrated that the nonlinearity difference of the bistability loops in the two pass bands of a uniform DFB-SLA could be enhanced greatly by asymmetric facet reflections [5]. A few years later, in another report, Hui showed that the bistability switching speed could be improved by increasing the bias level from below to above threshold [6].…”
Section: Introductionmentioning
confidence: 79%
“…The results are obtained for g 0 L D 1:21 for uniform, g 0 L D 0:63 for QWS, and g 0 L D 2:81 for tapered grating DFB-SLAs, which correspond to three equal transmission peaks (G) centered about the normalized detunings of ıL D 7:2, 1.58, and The active layer refractive index 3.553 -n 4 The buffer layer refractive index 3.405 -n 5 The 1.0, respectively. In fact, these results demonstrate that by introducing a phase shift to the uniform grating, the feedback tends to increase.…”
Section: Steady-state Characteristicsmentioning
confidence: 99%
“…The product of all transfer matrices yields a total transfer matrix which characterizes propagation through the entire amplifier. Although we neglect facet reflections throughout this paper, nonzero facet reflectivities can be included in a straightforward manner [14], [17].…”
Section: Small-signal Amplificationmentioning
confidence: 99%
“…Optical bistability in DFB SLA's has been theoretically studied for amplifiers with uniform gratings, where an average intensity distribution was (appropriately) used [15]- [17]. Grating nonuniformities, however, cause the intensity distribution to vary significantly within a DFB device.…”
Section: Introductionmentioning
confidence: 99%